Adherence-adjusted estimates of benefits and harms from treatment with amoxicillin for LRTI: secondary analysis of a 12-country randomised placebo-controlled trial using randomisation-based efficacy estimators. Issue 3 (6th March 2015) - Gillespie, David; Hood, Kerenza; Farewell, Daniel; Butler, Christopher C; Verheij, Theo; Goossens, Herman; Stuart, Beth; Mullee, Mark; Little, Paul; ,
Abstract : Objectives: Estimate the efficacy of amoxicillin for acute uncomplicated lower-respiratory-tract infection (LRTI) in primary care and demonstrate the use of randomisation-based efficacy estimators. Design: Secondary analysis of a two-arm individually-randomised placebo-controlled trial. Setting: Primary care practices in 12 European countries. Participants: Patients aged 18 or older consulting with an acute LRTI in whom pneumonia was not suspected by the clinician. Interventions: Amoxicillin (two 500 mg tablets three times a day for 7 days) or matched placebo. Main outcome measures: Clinician-rated symptom severity between days 2–4; new/worsening symptoms and presence of side effects at 4-weeks. Adherence was captured using self-report and tablet counts. Results: 2061 participants were randomised to the amoxicillin or placebo group. On average, 88% of the prescribed amoxicillin was taken. The original analysis demonstrated small increases in both benefits and harms from amoxicillin. Minor improvements in the benefits of amoxicillin were observed when an adjustments for adherence were made (mean difference in symptom severity −0.08, 95% CI −0.17 to 0.01, OR for new/worsening symptoms 0.81, 95% CI 0.66 to 0.98) as well as minor increases in harms (OR for side effects 1.32, 95% CI 1.12 to 1.57). Conclusions: Adherence to amoxicillin was high, and the findings from the original analysis were robust to non-adherence. Participants consulting to primary care with an acute uncomplicated LRTI can on average expect minor improvements in outcome from taking amoxicillin. However, they are also at an increased risk of experiencing side effects. Trial registration numbers: Eudract-CT 2007-001586-15 and ISRCTN52261229 . The trial was registered at EudraCT in 2007 due to an administrative misunderstanding that EudraCT was a suitable registry—which it was not in 2007, but has become since. On discovery of this error, the trial was also registered at ISRCTN (January 2009). Trial procedures did not change between the two registrations.